The challenge of promoting self-regulated learning among primary school children with a low socioeconomic and immigrant background. Issue 2 (4th March 2017) - Vandevelde, Sabrina; Van Keer, Hilde; Merchie, Emmelien
ABSTRACT: The authors explore the effects of student tutoring as an approach to provide support on self-regulated learning (SRL) to fifth- and sixth-grade students with a low socioeconomic or immigrant background. In total, 401 Flemish (Belgium) students participated. A quasi-experimental study with pretest, posttest, and retention test control group design was used, combining teacher ratings, self-report questionnaires, and think-aloud protocols. The teacher rating results show a significantly positive effect from pretest to posttest for the experimental condition, but this was not maintained at the retention test. The questionnaire and think-aloud results reveal no significant effects on students' SRL. However, differential effects depending on students' motivational profile were found. This study illustrates the complexity of promoting SRL among primary school children with a low socioeconomic or immigrant background, recommending further research into conditions and factors influencing the effectiveness of student tutoring programs promoting SRL.